Anabolic Steroids-Driven Regulation of Porcine Ovarian Putative Stem Cells Favors the Onset of Their Neoplastic Transformation - Gabriela Gorczyca (MDPI AG, 2021)
Nandrolone (Ndn) and boldenone (Bdn), the synthetic testosterone analogues with strong anabolic effects, despite being recognized as potentially carcinogenic compounds, are commonly abused by athletes and bodybuilders, which includes women, worldwide. This study tested the hypothesis that different doses of Ndn and Bdn can initiate neoplastic transformation of porcine ovarian putative stem cells (poPSCs). Immunomagnetically isolated poPSCs were expanded ex vivo in the presence of Ndn or Bdn, for 7 and 14 days. Results show that pharmacological doses of both Ndn and Bdn, already after 7 days of poPSCs culture, caused a significant increase of selected, stemness-related markers of cancer cells: CD44 and CD133. Notably, Ndn also negatively affected poPSCs growth not only by suppressing their proliferation and mitochondrial respiration but also by inducing apoptosis. This observation shows, for the first time, that chronic exposure to Ndn or Bdn represents a precondition that might enhance risk of poPSCs neoplastic transformation. These studies carried out to accomplish detailed molecular characterization of the ex vivo expanded poPSCs and their potentially cancerous derivatives (PCDs) might be helpful to determine their suitability as nuclear donor cells (NDCs) for further investigations focused on cloning by somatic cell nuclear transfer (SCNT). Such investigations might also be indispensable to estimate the capabilities of nuclear genomes inherited from poPSCs and their PCDs to be epigenetically reprogrammed (dedifferentiated) in cloned pig embryos generated by SCNT. This might open up new possibilities for biomedical research aimed at more comprehensively recognizing genetic and epigenetic mechanisms underlying not only tumorigenesis but also reversal/retardation of pro-tumorigenic intracellular events.